Community Approaches to Sexual Assault: VAWA's Role and Survivors' Experiences. (January 2021) - Zweig, Janine; Farrell, Lauren; Walsh, Kelly; Yu, Lilly
This article reviews two types of community-based approaches to addressing sexual assault that survivors may encounter—sexual assault nurse examiners and victim advocates from nonprofit community agencies—and highlights ways that the Violence Against Women Act (VAWA) and its reauthorizations have influenced this work. We also review information on the intersections of the work of these providers with police and prosecutors and include how these relate to survivors' experiences. We conclude with thoughts that look forward to future research on these issues emphasizing authentic engagement of practitioners and survivors in the research process.